Community Resilience Pathways in Smallholder Farming Systems toward Sustnable Agricultural Transformation - Rita Parmawati (PT FORMOSA CENDEKIA GLOBAL, 2026)
The transformation of sustainable agriculture in small-scale farming systems is becoming increasingly important as farmers' vulnerability to climate change, market pressures, and limited access to resources increases. This study aims to identify community resilience pathways in smallholder communities and explain how adaptive capacity, livelihood strategies, and institutional support contribute to the direction of sustainable agriculture transformation. The case study was conducted in Poncokusumo District, Malang Regency, with a qualitative approach and data collection techniques in the form of in-depth interviews with 12 informants, accompanied by field observations and documentation of local agricultural programs. Data were analyzed using thematic analysis techniques to trace patterns of community resilience and social-ecological dynamics formed at the local level. The results show that the path of community resilience develops through diversification of farming businesses, strengthening social capital in farmer groups, and increasing access to information, innovation, and institutional facilitation, which strengthens farmers' ability to manage agricultural risks. In addition, the role of extension workers and village institutions serves as a strategic link in accelerating the adoption of sustainable cultivation practices. This study concludes that community resilience is a fundamental foundation for accelerating the transformation of sustainable agriculture in smallholder systems and makes a conceptual and practical contribution to the formulation of agricultural development strategies based on community resilience.